1986
DOI: 10.1111/j.1365-2362.1986.tb01347.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of stress hormones on lipid and carbohydrate metabolism in man with partial insulin deficiency

Abstract: The metabolic responses to 4-h infusions of adrenaline (3 micrograms kg-1 h-1) and cortisol (10 mg m-2 h-1 for 2 h followed by 5 mg m-2 h-1 for 2 h), separately and in combination, have been studied in six healthy subjects with concurrent somatostatin infusion (250 micrograms h-1). A combined infusion of adrenaline, cortisol, glucagon (180 ng kg-1 h-1) and somatostatin has also been studied. Somatostatin plus adrenaline and somatostatin plus cortisol resulted in hyperglycaemia (at 240 min, somatostatin plus ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Over and above prevailing glucocorticoid concentrations, a further critical confounder is the effect of other hormones regulating lipolysis, notably insulin and adrenaline . In vivo , the effect of interactions between cortisol and either adrenaline or insulin has been examined only once in humans, although systemic rates of lipolysis were not measured as the appropriate tracers were not infused. We hypothesized that the effects of glucocorticoids on lipolysis in humans are indirect and dependent on the prevailing insulin and/or adrenaline concentrations, with glucocorticoids augmenting the pro‐lipolytic effects of adrenaline and antagonizing the suppressive effects of insulin.…”
Section: Introductionmentioning
confidence: 99%
“…Over and above prevailing glucocorticoid concentrations, a further critical confounder is the effect of other hormones regulating lipolysis, notably insulin and adrenaline . In vivo , the effect of interactions between cortisol and either adrenaline or insulin has been examined only once in humans, although systemic rates of lipolysis were not measured as the appropriate tracers were not infused. We hypothesized that the effects of glucocorticoids on lipolysis in humans are indirect and dependent on the prevailing insulin and/or adrenaline concentrations, with glucocorticoids augmenting the pro‐lipolytic effects of adrenaline and antagonizing the suppressive effects of insulin.…”
Section: Introductionmentioning
confidence: 99%
“…Studies without tracer infusion have demonstrated that adrenaline and cortisol have synergistic effects on NEFA concentrations during somatostatin administration (Pernet et al 1986), but have no effect on the anti-lipolytic effect of insulin during hyperinsulinaemia (20 mU/m 2 per min; Clerc et al 1986). Both GH and glucocorticoids may influence sensitivity to adrenaline by reducing anti-lipolytic a 2 -adrenoreceptor availability (Yip & Goodman 1999, Djurhuus et al 2004), but acute in vivo studies have demonstrated additive independent effects of GH and cortisol on lipolysis during a pancreatic clamp, suggesting separate mechanisms of action (Djurhuus et al 2004).…”
mentioning
confidence: 99%